Rapid induction of somatic embryos and production of synthetic seeds from hempedu bumi (Andrographis paniculata) - a malay ethnomedicinal plant - Paritala Vikram; Ilfah Husna Abdullah Ripain; Kishore K. Chiruvella; Mohammed Arifullah (Universiti Malaysia Kelantan, 2015)
Hempedu Bumi, Andrographis paniculata a popular Malay ethnomedicinal plant used to treat various kinds of diseases like common cold, fever, liver disease and snake bite. Andrographolide a bitter compound present in the plant posses many medicinal properties like anti-inflammatory, antiviral, anti-HIV and promising anticancer activity. Large amount of the compound is being extracted from the plants so there is a need for commercial cultivation of this plant, but seed dormancy proved to be a major obstacle for this process. So production of non-dormant synthetic seeds is an alternative to the dormant natural seeds for the mass cultivation of this plant. Hence the present study is aimed to produce somatic embryos and synthetic seeds using plant tissue culture technique. The zygotic embryos from immature seeds of A. paniculata were inoculated on to MS media containing various auxins (NAA, IBA, 2, 4-D), and cytokinins (BAP, TDZ and Kinetin) for the induction of somatic embryos. Out of all the treatments used, only 1.5 mg/L NAA + 0.75 mg/L Kinetin produced somatic embryos after 6 weeks of culture and the number of somatic embryos per explant was 9.8 ± 0.6. NAA alone produced rhizogenic calli and NAA along with BAP produced hard friable white callus, 2, 4-D alone and 2, 4-D with cytokinins (BAP, Kinetin) produced creamy callus, while IBA alone and in combination with cytokinins (BAP, Kinetin), TDZ resulted in germination of embryos into seedlings. The somatic embryos produced were coated with sodium alginate solution and made into synthetic seeds. The synthetic seeds that have been produced can be used as planting material and for conservation of the plant for future uses.